1992
DOI: 10.1212/wnl.42.12.2279
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and interobserver reliability of scalp ictal EEG

Abstract: We studied the accuracy and reliability of scalp ictal EEG in 137 complex partial seizures (119 temporal and 18 extratemporal) in 35 patients in whom we knew the correct site of seizure origin because all patients had been seizure-free for more than 2 years after seizure surgery. Three electroencephalographers independently determined side of seizure origin based on activity at onset of electrographic seizure (ASO), rhythmic theta and alpha (RTA), postictal findings (PIF), and the electrographic seizure as a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
70
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(76 citation statements)
references
References 0 publications
5
70
1
Order By: Relevance
“…The percentage of correct lateralization based on initial ictal EEG features and rhythmic theta or alpha waves was similar to other studies 11,14 . There were no differences between the two groups for rhythmic waves presence, as reported by Burgerman et al 12 although O'Brien et al 15 have observed this EEG feature mainly in mesial seizures.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The percentage of correct lateralization based on initial ictal EEG features and rhythmic theta or alpha waves was similar to other studies 11,14 . There were no differences between the two groups for rhythmic waves presence, as reported by Burgerman et al 12 although O'Brien et al 15 have observed this EEG feature mainly in mesial seizures.…”
Section: Discussionsupporting
confidence: 89%
“…False lateralization occurred in one seizure of group 1 and in three temporal tumor patients of group 2, a phenomenon already described 40 . Postictal EEG lateralizatory findings were observed in 48% of the seizures and they correctly lateralized the EA in almost all of them, as reported by others 14,41 . Although we observed a high percentage of correct lateralization, the presence of postictal features in only about 50% of seizures in our casuistics limited its value, as was also observed in Walczak et al 14 study.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Dodrill et al (27), reported that ictal EEG recording was associated with a poorer outcome after ATL, but not all patients in the study received long-term monitoring. Others (8,33) have shown greater accuracy with ictal EEG. We found in this series of 78 patients that lateralization of ictal EEG was not contralateral to MRI and interictal EEG in the 61% of patients with concordant MRI and interictal scalp EEG abnormalities.…”
Section: Discussionmentioning
confidence: 98%
“…Among studies that used M 1 , T 1 sphenoidal, or sphenoidal electrodes supplementing the 10-20 system, the site of scalp-recorded seizures in temporal lobe epilepsy correlated with side of invasively recorded seizures or of effective lobectomy in 75-83% of cases (37)(38)(39)(40). Among 67 nonlesional temporal patients rendered SF by surgery, Williamson et al (41) found scalp ictal lateralizing "changes" ultimately appearing in 81% of patients; in 87% of these, the seizures occurred ipsilateral to depth EEG seizures and curative surgery.…”
Section: Scalp Eegmentioning
confidence: 99%